Penguatan Literasi Bahasa Indonesia Melalui Program Pojok Baca di Sekolah Dasar - Arozatulo Bawamenewi (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
The program to strengthen Indonesian literacy through the Reading Corner at Bagoa Samasi Elementary School, Gunungsitoli Idanoi District, Gunungsitoli City was carried out as an effort to increase students' interest in reading and literacy skills, which have been relatively low. This activity is part of community service in the Independent Campus program which involves students, teachers, students, and the community around the school. This program is designed through the provision of a Reading Corner that is child-friendly, attractive, and based on local wisdom. The method used is a participatory approach with data collection techniques through observation, interviews, and documentation. The results of the program implementation showed a significant increase in students' reading interest, reading and writing skills, and active participation of teachers and parents in literacy activities. In addition, the involvement of students as companions has a positive impact on strengthening their social and leadership skills. The Reading Corner model developed based on local culture has proven to be able to build a sustainable literacy ecosystem and can be replicated in other schools, especially in areas with limited literacy access. This program not only improves students' literacy competencies but also fosters a love for local culture and strengthens synergy between schools, students, and communities